Structured Ethical Reflection in Practitioner Inquiry: Theory, Pedagogy, and Practice. Issue 4 (1st October 2016) - Stevens, Douglas M.; Brydon-Miller, Mary; Raider-Roth, Miriam
Abstract: Practitioner inquiry provides a powerful tool for improving practice and addressing critical issues in classrooms, schools, and broader communities. However, it also raises unique ethical challenges that often go unrecognized and unresolved. Structured Ethical Reflection (SER) provides teacher researchers with a process for identifying core values and examining the ways in which these principles are embodied in research and pedagogical practice. This article examines SER from the perspectives of theory, pedagogy, and practice.